Standard manual capsulorhexis / Ultrasound phacoemulsification compared to femtosecond laser-assisted capsulorhexis and lens fragmentation in clear cornea small incision cataract surgery. Issue 1 (December 2016) - Kanellopoulos, Anastasios; Asimellis, George
Abstract Background Femtosecond-laser assisted clear cornea cataract surgery may hold promise in safer and more effective procedures. We decided to perform a comparative study to standard manual incision phacoemulsification surgery. Methods This is a single-center, single-intervention, and prospective comparative data evaluation of 133 consecutive cases subjected to cataract surgery. Group-A (Phaco), manual capsulorhexis & ultrasound phacoemulsification (n  = 66); Group-B femtosecond-laser assisted capsulorhexis and lens fragmentation (n  = 67), employing the LenSx laser (Alcon Surgical, Ft. Worth, TX). All cases were evaluated for refraction, visual acuity, keratometry, tomography, pachymetry, endothelial cell counts, intraocular pressure, and type of intraocular lens (IOL) implanted. The groups were matched for age, gender, pre-operative vision metrics, and cataract grade, and were followed up to 1 year. Results In group-A post-operative uncorrected distance visual acuity (UDVA) was 20/20 or better in 61.5 % and 20/25 or better in 78.5 % of the eyes. The femtosecond laser group-B had improved outcomes (p  = 0.075 andp  = 0.042, respectively): post-operative UDVA was 20/20 or better in 62.7 % of the eyes and 20/25 or better in 85.1 %. Linear regression scatterplots of achieved versus attempted spherical equivalent had excellent regression coefficients (r 2  = 0.983 in group-A and 0.979 in group-B). There were 75.2 % cases in group-A and 80.6 % in group-B (p  = 0.8732) within ±0.50 D of targeted refractive equivalent. Slight trend of under-correction was noted in group-A. Average residual manifest cylinder in the toric subgroup-A was -0.50 D (95 % Limit-of-Agreement (LoA) = -0.78 D), and in toric subgroup-B -0.45 D (LoA = -0.45 D). Conclusions Mean spherical equivalent refraction and visual acuity are comparable with laser cataract surgery compared with manual capsulorhexis & ultrasound phacoemulsification. Improved astigmatism correction may be among the benefits of femtosecond laser–assisted cataract surgery. Transient corneal edema may be a first day transient disadvantage in femtosecond laser–assisted cataract surgery.